GE_GERICHTE P/10202/2017 vom 18. November 2020 - GE Cour de justice (2020)
VIOLENCE DOMESTIQUE;IN DUBIO PRO REO;LÉSION CORPORELLE SIMPLE;PRINCIPE DE L'ACCUSATION;TORT MORAL | CP.123; CP.126; CPP.9; CPP.325; CO.49